Fermentation of gum arabic by gut microbiota using in vitro colon model - Ahallil, Hammad; Abdullah, Aminah; Maskat, Mohamad Yusof; Sarbini, Shahrul R. (AIP Publishing LLC, 2019)
At birth, the human colon is rapidly colonized by gut microbes. Owing to their vast number and their capacity to ferment prebiotics, these gastrointestinal microbes act as an environmental factor that affects the host’s physiology and metabolism, particularly in the context of obesity and its related metabolic disorders. In this study, we investigate the effect of gum Arabic (Acacia senegal) as potential prebiotic on human microbiota from obese donors. The effect of Acacia senegal tested using anaerobic, pH-controlled faecal batch cultures system inoculated with human faeces to mimic the distal colon of obese subject. The microbial composition and production of microbial metabolites were monitored at 0, 6, 12, 24 and 36 h using fluorescent in situ hybridization (FISH). Acacia senegal was found to modulate the microbiota population, since it significantly increase the growth of Bifidobacterium and decrease the growth of Clostridium. These results identify Acacia senegal as an additional contributing factor to the gut microbiota of obese subjects.